Identification of Water Vapour Transmission Rate (WVTR) of Aluminum Foil Packaging Barrier using The Gravimetric Testing Method - Syafira Syafira; Supardianningsih Supardianningsih; Mawan Nugraha (Politeknik Negeri Media Kreatif, 2018)
The packaging is the most important thing for packing the food product. The main function of packaging is protecting the product from external factors such as light, water vapour, oxygen, and humidity. Sometimes the damage of food products occurs because of the contaminations of water vapour like a clumping on powdered food products. However, aluminum foil is a good barrier to protect food products. The packaging barrier needs to be tested to assure which one is the best to protect food products, especially from water vapour. Water vapour transmission rates are used to test how much the vapour can be absorbed by the packaging and the test results can be used as a reference for product packaging. The identification of water vapour transmission absorbed on the aluminum foil is tested using the gravimetric testing method and refers to the ASTM E96 standard. The result shows the thicker aluminum foil has used to protect the food products, the lower they absorb water vapour.